Genomic Assessment of Potential Probiotic Lactiplantibacillus plantarum CRM56-2 Isolated from Fermented Tea Leaves - Engkarat Kingkaew; Naoto Tanaka; Yuh Shiwa; Jaruwan Sitdhipol; Rattanatda Nuhwa; Somboon Tanasupawat (Tropical Life Sciences Research, 2024)
Lactiplantibacillus plantarum is a widely studied species known for its probiotic properties that can help alleviate serum cholesterol levels. Whole-genome sequencing provides genetic information on probiotic attributes, metabolic activities and safety assessment. This study investigates the probiotic properties of strain CRM56-2, isolated from Thai fermented tea leaves, using Whole-Genome Sequencing (WGS) to evaluate the safety, health-promoting genes and functional analysis. Strain CRM56-2 showed bile salt hydrolase (BSH) activity, assimilated cholesterol at a rate of 75.94%, tolerated acidic and bile environments and attached to Caco-2 cells. Based on ANIb (98.9%), ANIm (99.2%), and digital DNA–DNA hybridisation (98.3%), strain CRM56-2 was identified as L. plantarum. In silico analysis revealed that it was not pathogenic and contained no antibiotic-resistance genes or plasmids. L. plantarum CRM56-2 possessed genes linked to several probiotic properties and beneficial impacts. The genome of strain CRM56-2 suggested that L. plantarum CRM56-2 is non-hazardous, with potential probiotic characteristics and beneficial impacts, which could enhance its probiotic application. Consequently, L. plantarum CRM56-2 demonstrated excellent cholesterol-lowering activity and probiotic properties.